The Role of Vitamin D and Vitamin D Receptor in Placenta Accreta Spectrum: A Literature Review - Putri Mirani; Peby Maulina Lestari; Krisna Murti; Iche Andriyani Liberty; Cindy Kesty; Hana Andrina; Bella Stevanny (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2023)
Objective: This study aims to review the role of vitamin D and vitamin D receptor in Placenta Accreta Spectrum Disorder (PASD)Method: This review used several databases, namely Google Scholar, Science Direct, Elsevier, Medline, PubMed, Proquest, dan Wiley Online Library to search original and review articles in English about placenta accreta spectrum, placenta accreta, vitamin D, and vitamin D receptor in the last 10 years. Other reference sources used were guidelines and textbooks.Results: A total of four articles were included in this review.Discussion: Placenta accreta spectrum disorder is becoming more common around the world, owing to the rise in cesarean deliveries. It is linked to several risk factors, including a lack of vitamin D. Vitamin D and its receptor stimulate endometrial decidualization, which aids implantation. Vitamin D receptors in human placental trophoblasts create and respond to 1,25(OH)2D3, which promotes the conversion of endometrial cells to decidual cells. Women with PASD are mostly suffering from vitamin D deficiency. Conclusion: Vitamin D levels may influence trophoblast invasion in PASD and can be a potential diagnostic marker.Peran Vitamin D dan Reseptor Vitamin D dalam Spektrum Plasenta Akreta: Suatu Tinjauan PustakaAbstrakTujuan: Penelitian ini bertujuan untuk meninjau peran vitamin D dan reseptor vitamin D dalam Spektrum Plasenta Akreta (SPA)Metode: Tinjauan pustaka ini menggunakan beberapa sumber data yaitu Google Scholar, Science Direct, Elsevier, Medline, PubMed, Proquest, dan Wiley Online Library untuk mencari artikel penelitian dan tinjauan pustaka dalam Bahasa Inggris mengenai plasenta akreta, vitamin D, dan reseptor vitamin D dalam 10 tahun terakhir. Sumber referensi lain yang digunakan adalah pedoman dan buku teks.Hasil: Sebanyak empat artikel dimasukkan dalam ulasan ini.Diskusi: Spektrum Plasenta Akreta terjadi lebih sering di seluruh dunia karena meningkatnya persalinan sesar. Plasenta akreta terkait dengan beberapa faktor risiko termasuk kekurangan vitamin D. Vitamin D dan reseptornya merangsang desidualisasi endometrium dan berperan dalam implantasi. Reseptor vitamin D pada trofoblas plasenta membuat dan merespons 1,25(OH)2D3 yang mendorong konversi sel endometrium menjadi sel desidua. Mayoritas wanita dengan SPA mengalami kekurangan vitamin D.Kesimpulan: Kadar vitamin D dapat mempengaruhi invasi trofoblas pada SPA dan berpotensi menjadi penanda diagnostik.Kata kunci: spektrum plasenta akreta, reseptor vitamin D, vitamin D